Wstrzymanie wykonania zastępczej kary pozbawienia wolności w trybie art. 65a k.k.w. - Muszyńska, Anna; Jaskóła, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article is devoted to the issue of criminal liability for the crime of attempt against one’s life by the aggrieved as an aggravated type of stalking. It is related to validity of penalisation of this type of behaviour. It was pointed to interpretative doubts concerning appearances of a crime, as well as joining a discussion about bittiness within the scope of regularising the penal sanction.
Keywords: prześladowanie; przestępstwo; pokrzywdzenie; zamach na życie; nękanie